Analysis of the flow and heat transfer characteristics for MHD free convection in an enclosure with a heated obstacle - Parvin, S.; Nasrin, R. (Nonlinear Analysis: Modelling and Control, 2011)
Finite element method based on Galerkin weighted Residual approach is used to solve two-dimensional governing mass, momentum and energy equations for steady state, natural convection flow in presence of magnetic field inside a square enclosure. The cavity consists of three adiabatic walls and one constantly heated wall. A uniformly heated circular solid body is located at the centre of the enclosure. The aim of this study is to describe the effects of MHD on the flow and thermal fields in presence of such heated obstacle. The investigations are conducted for different values of Rayleigh number (Ra) and Hartmann number (Ha). Various characteristics of streamlines, isotherms and heat transfer rate in terms of the average Nusselt number (Nu) are presented for different parameters. The effect of physical parameter (D) is also shown here. The results indicate that the flow pattern and temperature field are significantly dependent on the above mentioned parameters.